2021
DOI: 10.25225/jvb.20043
|View full text |Cite
|
Sign up to set email alerts
|

A case study in canine detection of giant bullfrog scent

Abstract: Accurate survey methods are required for any wildlife research to yield reliable population data. This constraint finds significance in amphibian research that involves a highly threatened group of animals with a large proportion of cryptic species not easily detected by conventional survey methods. Across a growing spectrum of zoology research, survey outcomes are benefitting from the efficacy of scent detection dogs in assisting with species detection. We investigated the ability of a scent detection dog to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…body contact with target) depending on the needs of a project. Passive indication is recommended for CDD work to protect sample integrity and the safety of both the dog and wildlife (DeMatteo et al., 2019; MacKay et al., 2008; Matthew et al., 2021; Mosconi et al., 2017). However, details and definitions of CDD indications are regularly omitted in the literature.…”
Section: Factors Affecting Efficacy and Methodological Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…body contact with target) depending on the needs of a project. Passive indication is recommended for CDD work to protect sample integrity and the safety of both the dog and wildlife (DeMatteo et al., 2019; MacKay et al., 2008; Matthew et al., 2021; Mosconi et al., 2017). However, details and definitions of CDD indications are regularly omitted in the literature.…”
Section: Factors Affecting Efficacy and Methodological Issuesmentioning
confidence: 99%
“…For plant species, rates were high with 99% to 100% sensitivity and 85% to 100% precision (Goodwin et al., 2010; Needs et al., 2021; Vesely, 2008). Work with reptiles and amphibians reported rates of between 61% to 98% for sensitivity and 27% to 100% for precision (Browne et al., 2015; Cablk & Heaton, 2006; Engeman et al., 2002; Matthew et al., 2021; Stevenson et al., 2010; Witherington et al., 2017). CDDs detecting carcasses of birds and bats on windfarms were reported to show sensitivities between 71% and 96% (Arnett, 2006; Domínguez del Valle et al., 2020; Mathews et al., 2013; Smallwood et al., 2020).…”
Section: Efficacy Rates Across Contextsmentioning
confidence: 99%
“…This is an important aspect when training dogs to detect wildlife species such as T. cristatus, which are not always directly accessible at the surface [10,11]. Training of the handler is also important to ensure they are able to detect behavioural changes when diluted sources of the scent are encountered [15, see also 34,43]. It is however important to ensure that training with diluted scent solutions does not result in indications on residual scent, as during mitigation measures it is vital to locate the individuals only in occupied and not in vacated subterraneous shelters that may have retained the scent.…”
Section: Plos Onementioning
confidence: 99%
“…At present, projects involving detection dogs have only been conducted on a small number of amphibian species globally (e.g. North American salamanders: Amystoma californiense, Plethodon neomexicanus; South African giant bull frogs Pyxicephalus adspersus, Australian baw frog Philoria frosti; see [16,[32][33][34]). In Europe, a recent study found that detection dog teams were effective at locating both T. cristatus and smooth newts (Lissotriton vulgaris) in a variety of above ground surface refuges in tall and short grassland, as well as open and dense woodland habitat [35].…”
Section: Introductionmentioning
confidence: 99%
“…The next period runs approximately from 2010 to 2020 in which the field of biomedical detection dogs expands beyond cancer and into the variety of subdisciplines ( Table 2 ). This ten-year period is marked by an explosion of canine detection research resulting in a growing list of detectable human diseases by BMDDs and BMDDs able to detect virus [bovine viral diarrhea virus ( 10 )], bacteria [C. difficile ( 7 ), Escherichia coli, Klebsiella pneumoniae, Enterococcus faecalis, and Staphylococcus aureus ( 9 )], pests (brown tree snakes ( 22 ), palm weevils ( 23 ), gypsy moths ( 24 ), longhorn beetles ( 25 ), termites ( 26 ), bed bugs ( 27 ), and quagga and zebra mussels ( 28 ), fouling agents [catfight off-flavoring compounds ( 29 ), microbial growth in buildings ( 30 )], animals important to conservation efforts [grizzly and black bears ( 31 ), brown bears ( 32 ), geckos and tuataras ( 33 ), tortoises ( 34 ), quolls ( 35 ), jackals ( 36 ), giant bullfrogs ( 37 ), wolves ( 38 ), rabbits ( 39 ), rock ptarmigans ( 40 ), bats ( 41 ), koalas ( 42 ), kit foxes ( 43 ), tigers ( 44 ), cougars ( 45 ), cheetahs ( 46 ), bobcats ( 47 ), and gorillas ( 48 )], and disease odor directly on humans [Parkinson’s ( 49 ), epilepsy ( 50 ), diabetes ( 16 , 51 )].…”
Section: Introductionmentioning
confidence: 99%